Bibliometric profile on antisocial behaviors and physical aggression in school-going adolescents - De La Cruz Urbina, Katherin Lisset (2025)
Exploring disruptive behaviors in adolescents in basic education and their implications on their development is necessary to have updated information and support coherent measures. Therefore, the objective of this study was to evaluate the scientific literature on antisocial behaviors and physical aggression in adolescents enrolled in the Scopus database between 2010 and 2024. Scoping review was used as a method for bibliometric or retrospective studies, the terms used were: disruptive behavior, antisocial behaviour, deviant behavior, physical aggression, aggression, corporal aggression, adolescent together with Bolean operators AND, OR. The results of the study included 989 manuscripts, of which 81.2% were original empirical articles. The United States is the main country with the highest scientific production (41.7%) and the one with the greatest collaboration with European countries (United Kingdom, Germany and France) as well as countries such as Australia. The journals with the highest number of publications were the Journal of Child and Adolescent Psychopharmacology, Journal of the American Academy of Child and Adolescent Psychiatry (USA) and the terms widely used were adolescent and aggression. The main authors were Buitelaar, J.K., Banaschewski, T., and Franke, B. In summary, research on antisocial behaviors and physical aggression in adolescents has had a high representativeness and increase in recent years, mainly, these topics have been promoted by countries such as the United States, the United Kingdom and Canada. In addition to the fact that most journals come from these countries, there is a tendency to understand aggressive and antisocial behavior in men with respect to educational contexts.